ASSESSMENT OF THE INFLUENCE FACTORS OF FOREIGN DEBT ON THE MACROECONOMIC DEVELOPMENT OF THE COUNTRY - RAZINKOVA, Mіla (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article evaluates the factors influencing the external debt on the macroeconomic development of the country. Management of the external debt of the state involves a certain process of creation and implementation of a number of specific mechanisms of influence on such debt. It was established that the size of the external state debt depends on many factors, including the main economic indicators. It was determined that the external debt is not a static indicator of changes and can change its size under the influence of many factors: changes in taxation, changes in regulatory policy, changes in the foreign economic situation (for example, changes in the volume of external demand for export goods), changes in the economic situation, etc. When identifying cause-and-effect relationships between macroeconomic indicators, we will consider the ratio of the debt of the general public administration sector to GDP as a key indicator characterizing external public debt. The following indicators were used to find relationships: debt service to the total amount of state budget expenditures; consumer price index; index of the real effective exchange rate of the hryvnia to the US dollar; volume of direct foreign investment; volume of imports; index of political stability. Based on the results of modeling, we obtained the values of the investigated indicators, including their forecasts for the next 5 periods, as well as the range of deviations of the forecasted values. A cause-and-effect relationship between the ratio of the debt of the general public administration sector to the GDP of Ukraine and the selected group of macroeconomic indicators was revealed. Practical verification of the built model in the conditions of hostilities is impossible, which is caused by the catastrophic drop in GDP and the rapid increase in foreign aid of Ukraine's allies.
Keywords: foreign debt; state; macroeconomic development; factors; model